Amorphous low-temperature-resistant polyester composition and preparation method thereof
The amorphous low-temperature resistant polyester composition prepared by copolymerization and crosslinking reaction solves the problem of high brittleness of PET products in low-temperature environments, significantly improves impact strength and elongation of break, and broadens the application field of PET.
Patent Information
- Application Number
- CN202311310958.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-10-10
AI Technical Summary
PET products are highly brittle in low-temperature environments and are prone to rupture, which limits their application performance in low-temperature environments.
Through copolymerization and crosslinking reaction, reasonable alternating arrangement and molecular chain linking of different soft/hard segment molecular chains are achieved, and an amorphous low-temperature resistant polyester composition is prepared. The composition is prepared by esterification reaction and polycondensation reaction, and uses components such as refined terephthalic acid and phenylethylene glycol to form amorphous rigid structural unit and flexible structural unit of copolyester to reduce the crystallization ability and motion energy barrier between the molecular chains.
In low temperature environment, the impact strength of the sample is increased by more than 3 times and the elongation of break is increased by more than 5 times, which significantly improves the low temperature resistance of PET products, solves the problems of high brittleness and easy rupture, and broadens the application and use areas of PET.
Smart Images

Figure BDA0004487763520000021 
Figure BDA0004487763520000022 
Figure BDA0004487763520000023
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polyester, and specifically relates to an amorphous low-temperature-resistant polyester composition and a preparation method thereof. Background Art
[0002] Polyethylene terephthalate (PET) is a semi-crystalline polymer with excellent optical properties and weather resistance. Amorphous PET plastic has good optical transparency. In addition, PET plastic has excellent wear resistance, dimensional stability and electrical insulation. Bottles made of PET have high strength, good transparency, non-toxicity, anti-penetration, light weight, high production efficiency, etc., and are therefore widely used.
[0003] However, PET is mainly composed of benzene rings, has strong rigidity, and its glass transition temperature (Tg) is between 78 and 80°C. The lower the ambient temperature of PET products, the more brittle the material becomes, and it is very easy to break, which poses a safety hazard. Under room temperature conditions, the impact strength of standard samples of PET is about 50 to 60 J / m, while in a -20°C environment, the impact strength of standard samples is less than 20 J / m. This shortcoming of PET limits its application performance in low-temperature environments. Therefore, modifying PET and improving its low-temperature resistance can broaden its application areas and usage areas, which is of great practical significance.
[0004] Chinese patent CN108034204A discloses a low temperature impact resistant polyester composition and its preparation method. The low temperature impact resistant polyester composition is composed of the following raw materials: PBT resin, POK, TPEE elastomer, MBS toughening agent, compatibilizer, ester exchange inhibitor, antioxidant and lubricant, etc. The composition is blended by twin screws.
[0005] Chinese patent CN103042780A discloses a low-temperature-resistant biaxially stretched polyester film and a preparation method thereof. The polyester film comprises a substrate layer, and low-temperature-resistant layers are arranged on both sides of the substrate layer; the low-temperature-resistant layers comprise 20-60% of polyester material, 20-60% of thermoplastic elastomer and 5-20% of low-temperature toughening composition.
[0006] Chinese patent CN105255149A discloses a low-temperature toughened and reinforced PC / PBT alloy material and its preparation method, which improves the low-temperature impact performance of the alloy by adding a low-temperature toughening agent. However, the impact performance and heat resistance of the alloy material at room temperature are not disclosed. In addition, the addition amount of PC is about 50%, which makes the manufacturing cost of the alloy too high.
[0007] Chinese patent CN1020939545A discloses a method for preparing 2-methyl-1,3-propylene terephthalate and its copolyester elastomers, which discloses that a specific dibasic acid and a diol are subjected to an esterification reaction, and then a polyether glycol is added, and then a reduced pressure polycondensation is performed to obtain a poly(2-methyl-1,3-propylene terephthalate) and its copolyester elastomers.
[0008] Existing patents mainly improve the impact resistance and low temperature resistance of polyester matrix by blending or copolymerizing POK, TPEE elastomer, MBS toughening agent, low temperature toughening composition, polyether diol and PC in PET or PBT matrix. However, the above solutions, such as adding POK, TPEE elastomer, MBS toughening agent and PC, have poor compatibility with polyester matrix, which affects the transparency of the product and is also costly. After the polyester molecular chain is stretched and oriented, the intermolecular force perpendicular to the orientation direction is still weak, and there is still a risk of product rupture. Summary of the invention
[0009] The present invention provides an amorphous low-temperature-resistant polyester composition in view of the defects of the prior art, and solves the problem that the existing PET products are brittle and easily broken in low-temperature use environments. The present invention realizes the reasonable alternating arrangement of different soft / hard segment molecular chains through copolymerization reaction, and realizes the molecular chain connection between different molecular chains through cross-linking reaction, thereby obtaining an amorphous low-temperature-resistant polyester composition. The product prepared from the composition has the characteristics of no crystallization, good transparency, excellent low-temperature resistance, etc.
[0010] The purpose of the present invention can be achieved through the following technical solutions:
[0011] An amorphous low-temperature-resistant polyester composition, the structural formula of the composition is as follows:
[0012] R1
[0013]
[0014] Wherein: R2, R3 and R4 are independently selected from A structural unit, B structural unit or OH;
[0015] A structural unit:
[0016]
[0017] B structural unit:
[0018]
[0019] Among them: the number of n1 structural units: 10 to 25; the number of n2 structural units: 75 to 90.
[0020] A method for preparing the above-mentioned amorphous low-temperature-resistant polyester composition, the steps of the method are as follows:
[0021] The composition comprises an amorphous component A and an amorphous component B. The monomers of the amorphous component A are dibasic acid a and diol a, and are prepared by esterification reaction and polycondensation reaction under the action of a catalyst; the monomers of the amorphous component B are dibasic acid b and diol b, and polyol is used as a branching agent. Under the action of a catalyst, an esterification reaction and a polycondensation reaction are carried out, and the amorphous component A is added during the polycondensation reaction. After the reaction is completed, the reaction is cooled and granulated to obtain an amorphous low-temperature resistant polyester composition masterbatch.
[0022] In the technical solution of the present invention: in the amorphous component A, the dibasic acid a is a mixture of purified terephthalic acid and isophthalic acid, the diol a is 1,4-butanediol, and the catalyst is antimony ethylene glycol, tetrabutyl titanate or germanium dioxide.
[0023] In the technical solution of the present invention: in the amorphous component A, the amount of the metal element in the catalyst is 50 to 200 μg / g.
[0024] In the technical solution of the present invention, isophthalic acid accounts for 20-30% of component A.
[0025] In the technical solution of the present invention, in the amorphous component B, the dibasic acid b is purified terephthalic acid, the diol b is one or more of ethylene glycol, phenyl glycol, pentaerythritol, 1,4-cyclohexanedimethanol and spirodiol; the branching agent is at least one of propylene glycol, pentaerythritol and trimethylolpropane; the catalyst is antimony ethylene glycol, tetrabutyl titanate or germanium dioxide. It is further preferred that: the diol b is ethylene glycol, phenyl glycol and pentaerythritol; or the diol b is ethylene glycol, phenyl glycol and propylene glycol; or the diol b is ethylene glycol, phenyl glycol, 1,4-cyclohexanedimethanol and trimethylolpropane; or the diol b is ethylene glycol, phenyl glycol and trimethylolpropane.
[0026] In the technical solution of the present invention: in the amorphous component B, the amount of the catalyst metal element is 5 to 200 μg / g.
[0027] In the technical solution of the present invention: in the amorphous component B, the diol b is phenyl glycol, and the phenyl glycol accounts for 15-30% of the component B.
[0028] In the technical solution of the present invention: the amorphous component B accounts for 75-90% of the amorphous low-temperature resistant polyester composition.
[0029] In the technical solution of the present invention, when the intrinsic viscosity of the polycondensation reaction is 0.65-0.85 dL / g, the amorphous component A is added.
[0030] In the technical solution of the present invention: the benzene ring structure of purified terephthalic acid and phenyl glycol is used to form the amorphous rigid structural unit of the copolyester. The benzene ring of phenyl glycol is on the side of the molecular chain, so that the distance between local molecular chains is increased, and the "holes" between molecular chains are increased, providing a buffer space for the slip of the molecular chains, and the impact strength of the composition can be increased even in a low temperature environment.
[0031] In the technical solution of the present invention, purified terephthalic acid, isophthalic acid and 1,4-butanediol are used to form amorphous flexible structural units, which reduces the energy barrier of the local molecular chain moving in a low temperature environment (such as Figure 1 The “energy absorption” effect is achieved through deformation.
[0032] In the technical solution of the present invention, the crystallization ability of PET is reduced through amorphous design, the degree of entanglement between molecular chains is increased, the defect of insufficient interaction between molecular chains is solved, and the transparency of the product is improved.
[0033] In the technical solution of the present invention: different linear molecular chains are connected by a branching agent to increase the interaction between the molecular chains, further compensating for the low interaction between the linear polymer molecules (such as Figure 1 , Figure 2 ).
[0034] Beneficial effects of the present invention:
[0035] The present invention realizes the reasonable alternating arrangement of different soft / hard segment molecular chains through copolymerization reaction, realizes the molecular chain connection between different molecular chains through cross-linking reaction, and obtains an amorphous low-temperature resistant polyester composition. The product prepared from the composition has the characteristics of non-crystallization, good transparency, excellent low-temperature resistance, etc. Compared with conventional PET with the same characteristic viscosity under low-temperature environment, the impact strength of the sample is increased by more than 3 times, and the elongation at break is increased by more than 5 times, which solves the problem that the existing PET products are brittle and easy to break in low-temperature use environments. It broadens the application field and use area of PET and has great market prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Schematic diagram of the rupture direction of conventional PET products.
[0037] Figure 2 Example 1 Schematic diagram of the arrangement of amorphous low-temperature resistant molecular chains.
[0038] Note: The arrow represents the force direction, which is perpendicular to the molecular chain arrangement direction, i.e. the direction in which the product is prone to rupture. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto:
[0040] Comparative Example 1:
[0041] In a polyester reactor, 350g of purified terephthalic acid, 209g of ethylene glycol, 200μg / g of ethylene glycol antimony, and 50μg / g of sodium acetate are prepared into a slurry and put into an esterification reactor. The esterification reaction temperature is 220-260°C. After the esterification reaction, the mixture enters a final shrinkage reactor for a condensation reaction at a temperature of 275-285°C. After the polymerization reaction is completed, the melt is cooled and granulated to obtain a particle characteristic viscosity of 0.80dL / g; refer to the polyester test standard (GB17931-2003).
[0042] Comparative Example 2:
[0043] (1) 267.5 g of purified terephthalic acid, 132.5 g of isophthalic acid (accounting for 25% of the total amount of polyester), 400 g of 1,4-butanediol, and 50 μg / g of tetrabutyl titanate (calculated as titanium element) were mixed and slurried, and added to a reactor. The esterification reaction temperature was 220-240°C. After the esterification reaction, the mixture was placed in a final reduction reactor for polycondensation reaction at a temperature of 250-260°C. After reaching the predetermined reaction endpoint, the melt was cooled and granulated to obtain a slice with a characteristic viscosity of 0.80 dL / g.
[0044] (2) 400 g of purified terephthalic acid, 240 g of ethylene glycol, 500 μg / g of propylene glycol, and 150 μg / g of ethylene glycol antimony (calculated as antimony element) were mixed and slurried, and added to a reactor. The esterification reaction temperature was 220-260°C. After the esterification reaction, the mixture was placed in a final reduction reactor for polycondensation reaction at a temperature of 270-285°C. When the melt intrinsic viscosity reached 0.88 dL / g, the slices prepared in step 1 were added to the reactor at a mass ratio of 25%. After the reaction was continued for 0.5 hour, the melt was cooled and granulated to obtain slices of an amorphous low-temperature-resistant composition with an intrinsic viscosity of 0.90 dL / g.
[0045] Embodiment 1:
[0046] (1) 294 g of purified terephthalic acid, 106 g of isophthalic acid (accounting for 20% of the total amount of polyester), 400 g of 1,4-butanediol, and 200 μg / g of tetrabutyl titanate (calculated as titanium element) were mixed and slurried, and added to a reactor. The esterification reaction temperature was 220-260° C. After the esterification reaction, the mixture was placed in a final reduction reactor for polycondensation reaction at a temperature of 255-265° C. After reaching a predetermined reaction end point, the melt was cooled and granulated to obtain a slice with an intrinsic viscosity of 0.80 dL / g. The obtained polymer structure was recorded as structural formula 1, and the number average molecular weight was 34528.
[0047] (2) 400 g of purified terephthalic acid, 240 g of ethylene glycol, 138.6 g of phenyl glycol (accounting for 30% of the total amount of polyester), pentaerythritol, and 200 μg / g of ethylene glycol antimony (calculated as antimony element) were mixed and slurried, and added to a reactor. The esterification reaction temperature was 220-260° C. After the esterification reaction, the mixture was placed in a final reduction reactor for polycondensation reaction at a temperature of 270-285° C. When the melt intrinsic viscosity reached 0.65 dL / g, a polymer structure was obtained, which was recorded as structural formula 2 and had a number average molecular weight of 20175. The slices prepared in step 1 were added to the reactor at a mass ratio of 10%. After the reaction was continued for 0.5 hour, the melt was cooled and granulated to obtain slices of amorphous low-temperature-resistant composition, with an intrinsic viscosity of 0.70 dL / g and a number average molecular weight of 29525.
[0048]
[0049] In the following Examples 2 to 5, the structural formula nomenclature is the same as in Example 1, and the number average molecular weight is shown in Table 1.
[0050] Embodiment 2:
[0051] (1) 267.5 g of purified terephthalic acid, 132.5 g of isophthalic acid (accounting for 25% of the total amount of polyester), 400 g of 1,4-butanediol, and 50 μg / g of tetrabutyl titanate (calculated as titanium element) were mixed and slurried, and added into a reactor. The esterification reaction temperature was 220-240°C. After the esterification reaction, the mixture was placed into a final reduction reactor for polycondensation reaction. The polycondensation temperature was 250-260°C. When the predetermined reaction endpoint was reached, the melt was cooled and granulated to obtain a slice with an intrinsic viscosity of 0.95 dL / g.
[0052] (2) 400 g of purified terephthalic acid, 240 g of ethylene glycol, 92.4 g of phenyl glycol (accounting for 20% of the total amount of polyester), 500 μg / g of glycerol, and 150 μg / g of ethylene glycol antimony (calculated as antimony element) were mixed and slurried, and added to a reactor. The esterification reaction temperature was 220-260°C. After the esterification reaction, the mixture was placed in a final reduction reactor for polycondensation reaction at a temperature of 270-285°C. When the melt intrinsic viscosity reached 0.85 dL / g, the slices prepared in step 1 were added to the reactor at a mass ratio of 25%. After the reaction was continued for 0.5 hour, the melt was cooled and granulated to obtain amorphous low-temperature resistant composite slices with an intrinsic viscosity of 0.90 dL / g.
[0053]
[0054] Embodiment 3:
[0055] (1) 240 g of purified terephthalic acid, 159 g of isophthalic acid (accounting for 30% of the total amount of polyester), 400 g of 1,4-butanediol, and 80 μg / g of tetrabutyl titanate (calculated as titanium element) were mixed and slurried, and added into a reactor. The esterification reaction temperature was 220-250°C. After the esterification reaction, the mixture was placed into a final reduction reactor for polycondensation reaction. The polycondensation temperature was 250-260°C. When the predetermined reaction endpoint was reached, the melt was cooled and granulated to obtain a slice with an intrinsic viscosity of 1.0 dL / g.
[0056] (2) 400 g of purified terephthalic acid, 240 g of ethylene glycol, 69.3 g of phenyl glycol (accounting for 15% of the total amount of polyester), propylene glycol, and 5 μg / g of tetrabutyl titanate (calculated as titanium element) were mixed and slurried, and added to a reactor. The esterification reaction temperature was 220-260°C. After the esterification reaction, the mixture was placed in a final reduction reactor for polycondensation reaction at a temperature of 270-285°C. When the melt intrinsic viscosity reached 0.75 dL / g, the slices prepared in step 1 were added to the reactor at a mass ratio of 15%. After the reaction was continued for 0.5 hour, the melt was cooled and granulated to obtain amorphous low-temperature-resistant composite slices with an intrinsic viscosity of 0.80 dL / g.
[0057]
[0058] Embodiment 4:
[0059] (1) 267.5 g of purified terephthalic acid, 132.5 g of isophthalic acid (accounting for 25% of the total amount of polyester), 400 g of 1,4-butanediol, and 100 μg / g of tetrabutyl titanate (calculated as titanium element) were mixed and slurried, and added into a reactor. The esterification reaction temperature was 220-240°C. After the esterification reaction, the mixture was placed into a final reduction reactor for polycondensation reaction. The polycondensation temperature was 250-260°C. When the predetermined reaction end point was reached, the melt was cooled and granulated to obtain a slice with a characteristic viscosity of 0.95 dL / g.
[0060] (2) 400 g of purified terephthalic acid, 240 g of ethylene glycol, 83.2 g of phenyl glycol (accounting for 18% of the total amount of polyester), 46.2 g of 1,4-cyclohexanedimethanol, 800 μg / g of trimethylolpropane, 5 μg / g of tetrabutyl titanate (in terms of titanium element), and 100 μg / g of germanium dioxide were mixed and slurried, and added to a reactor. The esterification reaction temperature was 220-260°C. After the esterification reaction, the mixture was placed in a final reduction reactor for polycondensation reaction at a temperature of 270-285°C. When the melt intrinsic viscosity reached 0.70 dL / g, the slices prepared in step 1 were added to the reactor at a mass ratio of 20%. After the reaction was continued for 0.5 hour, the melt was cooled and granulated to obtain amorphous low-temperature resistant composite slices with an intrinsic viscosity of 0.80 dL / g.
[0061]
[0062] Embodiment 5:
[0063] (1) 278 g of purified terephthalic acid, 122 g of isophthalic acid (accounting for 23% of the total amount of polyester), 400 g of 1,4-butanediol, and 50 μg / g of tetrabutyl titanate (calculated as titanium element) were mixed and slurried, and added into a reactor. The esterification reaction temperature was 220-240°C. After the esterification reaction, the mixture was placed into a final reduction reactor for polycondensation reaction. The polycondensation temperature was 250-260°C. When the predetermined reaction end point was reached, the melt was cooled and granulated to obtain a slice with a characteristic viscosity of 0.95 dL / g.
[0064] (2) 400 g of purified terephthalic acid, 240 g of ethylene glycol, 129.4 g of phenyl glycol (accounting for 28% of the total amount of polyester), 400 μg / g of trimethylolpropane, and 90 μg / g of germanium dioxide (calculated as germanium element) were mixed and slurried, and added to a reactor. The esterification reaction temperature was 220-260° C. After the esterification reaction, the mixture was placed in a final reduction reactor for polycondensation reaction at a temperature of 270-285° C. When the intrinsic viscosity of the melt reached 0.70 dL / g, the slices prepared in step 1 were added to the reactor at a mass ratio of 20%. After the reaction was continued for 0.5 hour, the melt was cooled and granulated to obtain slices of an amorphous low-temperature-resistant composition with an intrinsic viscosity of 0.80 dL / g.
[0065]
[0066] The slices prepared in the above experiment were dried and then made into standard specimens using a micro injection molding machine. After being frozen at -24°C for 12 hours, the mechanical properties of the specimens were tested.
[0067] Table 1 Experimental sample test performance data
[0068]
Claims
1. An amorphous low-temperature-resistant polyester composition, characterized in that: The structural formula of the composition is as follows: Wherein: R2, R3 and R4 are independently selected from A structural unit, B structural unit or OH; A structural unit: B structural unit: Among them: the number of n1 structural units: 10 to 25; the number of n2 structural units: 75 to 90.
2. A method for preparing the amorphous low-temperature-resistant polyester composition according to claim 1, characterized in that: The steps of this method are as follows: The composition comprises an amorphous component A and an amorphous component B. The monomers of the amorphous component A are dibasic acid a and diol a, and are prepared by esterification reaction and polycondensation reaction under the action of a catalyst; the monomers of the amorphous component B are dibasic acid b and diol b, and polyol is used as a branching agent. Under the action of a catalyst, an esterification reaction and a polycondensation reaction are carried out, and the amorphous component A is added during the polycondensation reaction. After the reaction is completed, the reaction is cooled and granulated to obtain an amorphous low-temperature resistant polyester composition masterbatch.
3. The amorphous low-temperature-resistant polyester composition according to claim 2, characterized in that: In the amorphous component A, the dibasic acid a is a mixture of purified terephthalic acid and isophthalic acid, the diol a is 1,4-butanediol, and the catalyst is antimony ethylene glycol, tetrabutyl titanate or germanium dioxide.
4. The amorphous low-temperature-resistant polyester composition according to claim 3, characterized in that: In the amorphous component A, the amount of the metal element in the catalyst is 50 to 200 μg / g.
5. The amorphous low-temperature-resistant polyester composition according to claim 3, characterized in that: Isophthalic acid accounts for 20-30% of component A.
6. The amorphous low-temperature-resistant polyester composition according to claim 1, characterized in that: In the amorphous component B, the dibasic acid b is purified terephthalic acid, the diol b is one or more of ethylene glycol, phenyl glycol, pentaerythritol, 1,4-cyclohexanedimethanol and spirodiol; the branching agent is at least one of propylene glycol, pentaerythritol and trimethylolpropane; and the catalyst is antimony ethylene glycol, tetrabutyl titanate or germanium dioxide.
7. The amorphous low-temperature-resistant polyester composition according to claim 6, characterized in that: The amount of the catalyst metal element used is 5 to 200 μg / g.
8. The amorphous low-temperature-resistant polyester composition according to claim 5, characterized in that: The diol b is phenyl glycol, and phenyl glycol accounts for 15-30% of component B.
9. The amorphous low-temperature-resistant polyester composition according to claim 1, characterized in that: The amorphous component B accounts for 75-90% of the amorphous low-temperature-resistant polyester composition.
10. The amorphous low-temperature-resistant polyester composition according to claim 1, characterized in that: When the intrinsic viscosity of the polycondensation reaction is 0.65 to 0.85 dL / g, the amorphous component A is added.
Citation Information
Patent Citations
Low-temperature-resistant biaxially-oriented polyester film and preparation method thereof
CN103042780A
Low-temperature toughened and reinforced PC / PBT (polycarbonate / polybenzothiazole) alloy material and preparation method thereof
CN105255149A
Low-temperature-impact resistant polyester composition and preparation method thereof
CN108034204A
Low-melting point and transparent PET copolyester, its preparation method and application
CN103102473A
Amorphous polyester composition and preparation method and application thereof
CN105778065A
Cited By
High-transparency and high-impact amorphous copolyester and preparation method thereof
CN121136029A